Pengolahan Daur Ulang Minyak Bekas Menjadi Biodisel Untuk Sumber Energi Alternatif di Kelurahan Karya Merdeka Kabupaten Kutai Kertanegara - Andi Sri Irtawaty; Maria Ulfah; Armin Armin (Abdimas Universal, 2020)
Karya Merdeka Village is very famous for its oil palm plantations. Nearly 27% of the population work as oil palm farm laborers. In irrigating the plantations, they use diesel fueled rice cookers. Based on field surveys, 1 liter of diesel can be used for 2 hours to drive the dompeng machine. Means that in a month, residents need 30 liters of diesel fuel. If 1 liter costs IDR 6000, farmers will incur a cost of IDR 180,000 per month. Of course this needs to be balanced with an idea / innovation to reduce the expenditure of farmers in supplying diesel to their dompeng machines. Therefore, the Balikpapan State Polytechnic Lecturer team of the Electrical Engineering Department contributed significantly to the Community Service Activities (PkM) held at the Karya Merdeka Kelurahan Office, Kutai Kertanegara Regency in socializing a technology that can recycle used cooking oil into biodiesel, through a process of mixing with methanol and NaOH. The method of making it is quite simple, namely used cooking oil at a temperature of 40 degrees. For the right results, use a digital thermostat. The dose is 1 liter of used cooking oil mixed with half a liter of methanol and 0.1 mg NaOH. Stir until evenly distributed and leave for 24 hours. The result is biodiesel (clear color) and glycerol (the precipitate). Biodiesel is one alternative energy source that is environmentally friendly and proven to be economical in its implementation. It has the same function as Soilar, which is able to drive generators and dompeng engines, but is 3 times more efficient than diesel, which is 1 liter of biodiesel equivalent to 3 liters of diesel. It means that biodiesel is three times more efficient than diesel.